LASER IN PERIODONTOLOGY: A REVIEW OF THE FIELDS OF APPLICABILITY AND THERAPEUTIC EFFECTS - Ana-Petra Lazăr; Tiberiu Dinulescu; Timea Dako; Maria-Alexandra Mârţu; Mircea Suciu; Luminiţa Lazăr (Romanian Society of Oral Rehabilitation, 2022)
Lasers have multiple applications in periodontology, such as periodontal surgery and biostimulation adjuvant therapy for tissues affected by periodontal disease. Both high-power lasers such as Nd:YAG, Er:YAG, Er,Cr:YSGG or CO2, as well as low-power lasers like diode lasers, have demonstrated their applicability in the periodontal field over time, in surgeries with or without flaps, periodontal pocket decontamination or bone grafting interventions. In the treatment of peri-mucositis and peri-implantitis, the Er:YAG laser as well as the low-power diode laser produce beneficial effects for decontamination of implant surfaces without affecting the implant or soft tissue surrounding it. The property of stimulating cellular components and their modulation by the light source, led to the development of the photobiomodulation therapy concept, with anti-inflammatory, anti-allergic healing, and stimulation effects of cell growth factors. Emerging trends in this field are the use of laser in multiple periodontal surgery procedures, regeneration of soft and hard oral tissues, but also in stimulating the orthodontic tooth movement with anti-inflammatory and analgesic effects. The purpose of this article is to review the techniques of laser therapy used in the periodontal field and its effects on the soft and hard tissues.